The elves and the shoemaker - Galdone, Paul. (New York : Clarion Books, 1984)
When the poor shoemaker and his wife discover the two naked little elves who have helped them become successful, they sew fine outfits for them.
"Based on Lucy Crane's translation from the German of the Brothers Grimm."
Adaptation of: Die Wichtelmanner.
Mode of access: Internet.
Keywords: Folklore -- Germany -- Juvenile literature; Fairy tales